Platelet function is modified by common sequence variation in megakaryocyte super enhancers - Romina Petersen (Nature Portfolio, 2017)
Numerous genetic variants, including those located in the non-coding regions of the genome, are known to be associated with blood cells traits. Here, Frontini and colleagues investigate their potential regulatory functions using epigenomic data and promoter long-range interactions.